Study of kaon production at lower energy levels - Carroll, Lauren Mariah (My University, 2025)
Isaac Newton famously wrote, “It is inconceivable that inanimate brute matter should, without the mediation of something else which is not material, operate upon and affect other matter without mutual contact” (Newton, Isaac). This philosophical query ties into the mysteries that the Deep Underground Neutrino Experiment (DUNE) seeks to address. DUNE aims to explore fundamental questions such as the imbalance of matter and antimatter, supernova dynamics, and physics beyond the Standard Model. At its core, DUNE studies neutrinos, abundant subatomic particles with minimal mass and weak interactions, thus making them extremely difficult to detect. By examining how neutrinos interact and decay, DUNE aspires to deepen our understanding of the universe’s evolution and the underlying laws of physics. I am interested in looking at how DUNE’s project focuses on the cross sections of low-energy kaon particles, with the goal of improving their detection and calibration in liquid argon. Since DUNE is still under construction, I have been looking at how to use data from the prototype that will aid in identifying kaon decay and reducing confusion with similar particles. I am interested in learning more about refining kaon cross-section measurements to an accuracy of less than one percent and evaluating whether their detailed analysis significantly enhances particle research. Additionally, I have been researching how to combine the thin-slice and energy methods to produce a more accurate histogram of low-energy kaon production, thus contributing to DUNE’s broader mission of advancing particle physics.
Keywords: High energy physics; Neutrinos; Kaons